Enhancing Friction Stir Welding Performance: Finite Element Simulation Study using Filler Material - S. Rached; A. Chaabene; S. Chatti (Annals of "Dunarea de Jos" University of Galati, Fascicle XII, Welding Equipment and Technology)
Friction Stir Welding (FSW) is a groundbreaking method that revolutionizes welding by utilizing friction-induced heat to join metals without melting them. In this study, we conducted a comprehensive investigation into the FSW process using the numerical software Simufact Forming, focusing on the critical aspect of introducing filler material during the welding operation. Our work involved meticulous simulations to analyze the impact of filler material on the quality and integrity of the weld joint. Through detailed modelling and parameter optimization, we successfully demonstrated the significance of the refill stage in achieving superior welding outcomes. Our main results reveal a substantial enhancement in the weld joint's mechanical and metallurgical properties when filler material is strategically introduced. The simulations provided valuable insights into the optimal conditions for the refill stage, including tool movement, material feeding rates, and key process parameters. These findings contribute to the ongoing efforts in refining FSW techniques, facilitating the development of high-performance welded joints.